2008
DOI: 10.1002/bdd.604
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of decrease of oral bioavailability of cyclosporin A during immunotherapy upon coadministration of amphotericin B

Abstract: Running Title: Interaction of oral cyclosporin A/amphotericin B Abbreviations: CyA, cyclosporin A; AMB; amphotericin B; BA, bioavailability; CYP, cytochrome P450; P-gp, P-glycoprotein; DEX, dexamethasone; ALT, alanine aminotransferase; AST, aspartate aminotransferase; γ-GTP, γ-glutamyltranspeptidase; BUN, blood urea nitrogen; AUC 0-24h , area under the blood concentration-time curve from 0 to 24 h; MRT, mean residence time; CL tot , total clearance; Vd ss , distribution volume at the steady-state -1-ABSTRACT: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Consistent with our results, interaction between AMB and P-gp has been suggested by other pieces of evidence from studies on animal intestines (13,14,25). In a study by Ishizaki and colleagues, the oral bioavailability of cyclosporine was decreased after coadministration of AMB in Wistar rats, presumably due to the increased P-gp expression induced by AMB at the duodenum (14). Second, another research group demonstrated enhanced gastrointestinal absorption of AMB through formulating it in the oral lipid-based delivery system Peceol, which was able to decrease P-gp-mediated drug efflux by downregulating mdr1 mRNA in Caco-2 cells, also suggesting an interaction between this agent and P-gp (13,26).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our results, interaction between AMB and P-gp has been suggested by other pieces of evidence from studies on animal intestines (13,14,25). In a study by Ishizaki and colleagues, the oral bioavailability of cyclosporine was decreased after coadministration of AMB in Wistar rats, presumably due to the increased P-gp expression induced by AMB at the duodenum (14). Second, another research group demonstrated enhanced gastrointestinal absorption of AMB through formulating it in the oral lipid-based delivery system Peceol, which was able to decrease P-gp-mediated drug efflux by downregulating mdr1 mRNA in Caco-2 cells, also suggesting an interaction between this agent and P-gp (13,26).…”
Section: Discussionsupporting
confidence: 93%
“…2). Consistent with our results, interaction between AMB and P-gp has been suggested by other pieces of evidence from studies on animal intestines (13,14,25). In a study by Ishizaki and colleagues, the oral bioavailability of cyclosporine was decreased after coadministration of AMB in Wistar rats, presumably due to the increased P-gp expression induced by AMB at the duodenum (14).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…36 This is mediated via increased expression of the multidrug resistance gene MDR1 in the duodenum causing increased levels of the MDR1 gene product P-gp, 36 but it is not known if liposomal amphotericin has a similar effect. This results in increased efflux of ciclosporin and reduced plasma levels.…”
Section: Introductionmentioning
confidence: 99%
“…One study documented the drug-drug interactions of AmB and P-glycoprotein in the gastrointestinal tract (GIT). The authors demonstrated that AmB treatment significantly increased the level of P-glycoprotein, which resulted in a decrease in the oral bioavailability of cyclosporine in rats (30). Additional information on AmB interactions with efflux transporters, however, is not available; therefore, further studies should be performed.…”
Section: Discussionmentioning
confidence: 99%